2019
DOI: 10.1002/ente.201900819
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogenide Materials and Derivatives for Photovoltaic Applications

Abstract: Chalcogenide AB(S,Se)3 materials have recently attracted increased attention as they could simultaneously solve both the stability and toxicity issues faced by conventional perovskite solar cells. Computer‐aided design of metal chalcogenide semiconductors has experienced important progress over the past few years, leading to the discovery of very promising AB(S,Se)3 compounds and derivatives for application as absorbers in thin‐film photovoltaic devices. Experimental evidence demonstrates that the synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 92 publications
(112 reference statements)
2
42
0
1
Order By: Relevance
“…Such a phenomenon has also been observed in many classic thermoelectric materials, including PbX, Bi 2 X 3 , Cu 2 X, SnX (X = S, Se). [ 16,17 ] Although β ‐CsCu 5 Se 3 shows great performance in photovoltaic applications, [ 15,18 ] the research on its lattice thermal conductivity and thermoelectric properties has not been reported yet, which motivates us to carry out this study. On the basis of density functional theory (DFT) combined with semiclassical Boltzmann transport theory, we do find that β ‐CsCu 5 Se 3 possesses ultralow lattice thermal conductivities and a high ZT value, besides the reported photovoltaic features, exhibits high thermoelectric performance.…”
Section: Introductionmentioning
confidence: 99%
“…Such a phenomenon has also been observed in many classic thermoelectric materials, including PbX, Bi 2 X 3 , Cu 2 X, SnX (X = S, Se). [ 16,17 ] Although β ‐CsCu 5 Se 3 shows great performance in photovoltaic applications, [ 15,18 ] the research on its lattice thermal conductivity and thermoelectric properties has not been reported yet, which motivates us to carry out this study. On the basis of density functional theory (DFT) combined with semiclassical Boltzmann transport theory, we do find that β ‐CsCu 5 Se 3 possesses ultralow lattice thermal conductivities and a high ZT value, besides the reported photovoltaic features, exhibits high thermoelectric performance.…”
Section: Introductionmentioning
confidence: 99%
“…The ternary and quaternary metal Chalcogenide have attracted attention as promising candidates for solar cell materials because of their high photostability, environmentally earth‐abundant elements, relatively enormous absorption coefficient exceeding 10 4 cm −1 , non‐toxic, optimal direct energy gap between 1.0 eV and 1.6 eV. P‐type chalcogenide materials such as Cu 2 ZnSnSe 4 (CZTSe),Cu(In,Ga)Se 2 (CIGS),CdTe and Cu 2 ZnSnS 4 (CZTS) have already demonstrated efficiency of more than 20% on a laboratory scale 1,2 . The efficiency of CIGS solar cell is over 20%, while CZTS solar cell is about 12%.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of CIGS solar cell is over 20%, while CZTS solar cell is about 12%. However, the efficiency of kesterite‐based cells is till presently small Compared to Cu(In, Ga) Se 2 due to problems related to the material, such as defects and secondary phases 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…Since then, an α phase of CsCu 5 Se 3 has been achieved and proposed as a high-performance thermoelectric [10] and an ab-initio study treats the defect physics in CsCu 5 Se 3 and its potential in optoelectronics [11]. In a recent review on chalcogenides for photovoltaic applications, CsCu 5 Se 3 and other new chalcogenides are compared to their oxide analogs [12], to highlight opportunities for new materials.…”
Section: Introductionmentioning
confidence: 99%